2019
DOI: 10.1097/aog.0000000000003485
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use Without Indication During Delivery Hospitalizations in the United States

Abstract: OBJECTIVE: To analyze trends in unindicated antibiotic use during vaginal delivery hospitalization. METHODS: This study used an administrative database to analyze antibiotic use during delivery hospitalizations from January 2006 to March 2015. Women were classified by mode of delivery and whether they had an evidence-based indication for antibiotics. Indications for antibiotics included preterm prelabor rupture of membranes (PROM), cesarean delivery, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The proportion of women receiving unindicated antibiotics significantly decreased from 38.1% to 21.2% over a period of 10 years. 9 These findings indicate that evidence-based rationale for antibiotic use is becoming increasingly adopted into clinical practice in the USA. The study also showed that only having a standard protocol will not work.…”
Section: Available Knowledgementioning
confidence: 99%
“…The proportion of women receiving unindicated antibiotics significantly decreased from 38.1% to 21.2% over a period of 10 years. 9 These findings indicate that evidence-based rationale for antibiotic use is becoming increasingly adopted into clinical practice in the USA. The study also showed that only having a standard protocol will not work.…”
Section: Available Knowledgementioning
confidence: 99%
“…There are multiple reports of high levels of unnecessary prescriptions of antibiotics for both postnatal women, following either cesarean section (CS) or vaginal delivery, and neonates [ 10 13 ]. In Sub-Saharan Africa (SSA), although the risk of perinatal infections is high for both mothers and neonates, limited data exists on the use of antibiotics in these groups [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This near-universal prescription of antibiotics after CS is a common clinical practice in low income countries (20)(21)(22), despite the absence of an evidence base or recommendations to support it. By contrast, in high income countries, the irrational use of antibiotics after CS and in maternity wards has reported to have dropped markedly over recent years (10). This variation in practice may be explained by the onset of antibiotic stewardship programs in many hospitals in high-income countries (23).…”
Section: Discussionmentioning
confidence: 99%
“…In other low-income settings, high use of antibiotics in women with vaginal delivery has been reported in India and Vietnam, and in a WHO study combining data from Africa, Asia and the Americas (12,22,27).While the study in India reported the lack of local guidelines at the time of the study as a possible factor underlying the high antibiotic prescribing rate, it was not clear whether the Vietnamese and WHO studies were in facilities with availability of local or international guidelines for management. On the other hand, studies from Sweden and USA have reported a low use of antibiotics after vaginal delivery re ecting the well-established nature of antibiotic stewardship programs in these countries (10,23,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation